PENGARUH ONLINE CUSTOMER RATING DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN DITIKTOK SHOP MELALUI KEPERCAYAAN KONSUMEN SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA KONSUMEN TIKTOK SHOP SEMARANG) - Hijriyatunnisa, Hijriyatunnisa; Widodo, Untung (STIE PENA, 2024)
The purpose of this research is to determine the influence of online customer ratings and online customer reviews on purchasing decisions at the TikTok shop via consumer trust as an intervening variable in the TikTok application and to determine the influence of online customer ratings, online customer reviews, and consumer trust on purchasing decisions. The research method used in this research is path Analysis. The population of this research is TikTok shop consumers in the city of Semarang. The sample for this research was 120 people using a non-probability sampling technique with a purposive sampling approach, namely that the researcher selected the sample purposively, subjectively, and subjectively. The data collection method is to distribute questionnaires via Google Forms. The type of data used is primary data. The result of this research shows that online customer ratings influence consumer trust and online customer reviews influence customer trust. Online Customer Rating does not affect purchasing decisions, while Online Customer Reviews does not affect purchasing Decisions. Online Customer Ratings and Reviews influence purchasing decisions through consumer trust as an intervening variable in the TikTok application. Keywords: Online Customer Rating, Online Customer Review, Consumer Trust, Purchasing Decisions